2013
DOI: 10.4103/1319-3767.114507
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cap polyposis masquerading as ulcerative colitis with pseudopolyposis and presenting as chronic anemia: A case study with review of literature

Abstract: Cap polyposis (CP) is an under recognized form of non-neoplastic colonic polyps, characterised by the presence of inflammatory polyps with a distinct “cap” of granulation tissue. CP is often seen masquerading as chronic inflammatory bowel disease. The most common symptoms are mucoid diarrhoea, bloody stools, abdominal pain, and tenesmus. In this case report, we present a patient who was diagnosed with CP during the investigation of unexplained chronic long standing anemia secondary to intermittent rectal bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“… 3 Recto-sigmoid cap polyposis can lead to anemia from chronic blood loss, or to hypoalbuminemia from protein loss. 4 - 7 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Recto-sigmoid cap polyposis can lead to anemia from chronic blood loss, or to hypoalbuminemia from protein loss. 4 - 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed that polypoid lesions were mainly associated with mucosal prolapse syndrome, fibromuscular obliteration, and chronic straining at defecation. Also, its rarity often made physicians diagnose ulcerative colitis or another inflammatory bowel disease with pseudopolyps [ 3 , 6 , 8 , 9 ]. The exact etiology of cap polyposis remains unknown and several medical treatments, including aminosalicylates, antibiotics, steroids, and anti-inflammatory agents, have been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve cases of surgically treated cap polyposis were reported between 2004 and 2013, although several cases might have been experienced before 2002. In this reviewed series, last four cases [ 5 – 8 ] could not get the preoperative diagnosis of cap polyposis, and no case was confirmed which H. pylori was infected or not, and received H. pylori eradication therapy before any surgical treatment. One case underwent sigmoidectomy for cap polyposis and recurred after surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation